Dynamics of Jambi Malay Ethnic Group in The Political Contestation of Jambi Mayor Election - Ahmad, Jafar; Firmanda, Hengki (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2022)
Primordial loyalty that breeds fanaticism is often used by politicians as a shortcut and easy way to gather support. By using primordial interests, politicians do not need to work hard to gain support from the people. This research seeks to explain why Jambi Malay ethnic loyalty, as the dominant group, was not formed in relation to the Mayor Election in Jambi City. What are the factors that cause Malay ethnic sentiment not to appear. The data in this study were obtained through in-depth interviews, documentation, and news in the mass media. It is possible for the results of this study to be replicated in areas outside Jambi City to see whether the ethnic Malays elsewhere also have the same cultural roots, political attitudes, and habits, or vice versa. The results of this study will provide an explanation of the theoretical implications of the political events that occurred in the city of Jambi. The results of this study can be used to predict the future of Malay ethnic politics in the midst of an electoral democratic political system that is taking place in Indonesia.